Randomized Controlled Trial to Compare the Efficacy of Low-dose Daily vs Alternate-day Prednisolone in Children With Steroid Dependent and Frequently Relapsing Nephrotic Syndrome: Daily vs Alternate-day Prednisolone in Nephrotic Syndrome - Nain, Zulquar; Afzal, Kamran (Journal of Pediatric Nephrology, 2024)
Background and Aim: Tapering alternate-day doses of corticosteroid forms the cornerstone of the management of steroid-dependent nephrotic syndrome (SDNS) and frequently relapsing nephrotic syndrome nephrotic syndrome (FRNS). This study compares the reduction of relapses over a one-year follow-up, using equivalent steroid doses given as either daily or alternate-day therapy. Methods: This was an open-label, randomized controlled trial. The participants were children with SDNS or FRNS, aged 2-10 years. After remission, steroid doses were tapered until a threshold below 0.75 mg/kg/day. Then, subjects were randomized to one of two arms as follows: Daily prednisolone at 0.15-0.30 mg/kg/day (intervention arm) or alternate-day dose of 0.5-0.75 mg/kg (control arm). Both groups were compared after 12 months for a reduction in relapse frequency. Secondary outcome measures included time to first relapse, proportion of relapse-free patients, mean steroid dose used, infection episodes, need for alternative medications, and side effects of corticosteroids. Results: Median (interquartile range [IQR]) changes in relapse frequency did not differ between the groups, 0 (IQR: -1.0, 0.25) vs 0 (IQR: 0.0, 1.0) in intervention and control groups, respectively (P=0.46). The mean percentage change in relapse frequency was -18.1±42.4% (negative denotes decreased) in the intervention group and 6.0±26.9% in the control group (P=0.05). The median relapse frequencies during the trial period were 3 (IQR: 2, 3) and 3 (IQR: 3, 4) in the intervention group and control groups, respectively (P=0.021). At study completion, prednisolone dose was lower in the intervention group, 0.33±0.12 vs 0.40±0.05 (P=0.02). Both groups did not differ by other secondary outcome variables. Conclusion: In patients with SDNS and FRNS, daily low dose (0.15-0.30 mg/kg/day) administration of prednisolone is not superior to conventional alternate-day dosing.